2020
DOI: 10.3390/nu12092739
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Soy Protein Isolate Attenuates Intestinal Immunoglobulin and Mucin Expression in Young Mice Compared with Casein

Abstract: Dietary protein sources have profound effects on children and young animals, and are important for the gut barrier function and immune resilience. Milk and soy are the main sources of protein for children and young animals after weaning. The objective of this study was to compare the effects of dairy and soy proteins on the intestinal barrier in early development. Weanling C57BL/6 mice were fed AIN-93G diets prepared with casein or soy protein isolate (SPI) for 21 days. Compared with those fed with the casein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Future studies examining qualitative aspects of macronutrients, such as different types of fat and protein (i.e., animal vs. plant-based protein), would be required to fully appreciate the role of macronutrients on gut homoeostasis as well as on the host sIgA responses. For example, soy-derived protein has been associated with lower sIgA, compared to casein-derived protein 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Future studies examining qualitative aspects of macronutrients, such as different types of fat and protein (i.e., animal vs. plant-based protein), would be required to fully appreciate the role of macronutrients on gut homoeostasis as well as on the host sIgA responses. For example, soy-derived protein has been associated with lower sIgA, compared to casein-derived protein 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The activated STAT6 had been demonstrated to bind to a 554-bp IL-4 responsive enhancer in intron 1 of human PIGR gene in HT-29 cells to upregulate the expression of PIGR ( 47 ). It was reported that IL-4 mediated the transcription of pIgR via activating JAK1-STAT6 pathway in the intestines of mice ( 46 , 48 , 49 ). In present study, the levels of phosphorylated STAT6 were reduced in the intestines of EpCAM -/- mice, and the transcriptional levels of IL-4, Jak1 and Stat6 also reduced in the intestines of these mice.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for these differences is unclear, although a previous short-term study also observed faster growth in mice fed a soy-based compared to casein-based diet [ 40 ]. In an experiment of similar design, Zeng et al detected a small, but significantly higher rate of food intake of a soy-based control diet compared to the casein diet, but detected no effect on body weight [ 41 ]. In the present work, food intake did not differ between the 20% casein and 20% soy diets ( Figure 2 A).…”
Section: Discussionmentioning
confidence: 99%